Research on the Impact of the Emotional Expression of Kindergarten Teachers on Children: From the Perspective of the Class Micro-Power Relationship - Liu, Min; Wang, Qiong (Frontiers in Psychology, 2022)
In the preschool phase, the socio-emotional responses children receive from interactions with teachers are incorporated into their own social behaviors. This is one of the key ways in which children acquire social and emotional skills. Based on field studies, it can be found that this learning process is not simple imitation of children, but of a more complex context of group interaction. To further clarify the impact of kindergarten teachers' emotion on the sociometric status and behavior of children in their classes, the researcher chose a Montessori mixed-age kindergarten in Beijing as the field site and used an ethnographic approach to observe five classes within the kindergarten over a two-month period. The study found that the power gap between teacher and pupil spreads rapidly to all children in the classroom as a result of the teacher's emotions, and even stimulates power stratification within the children. There are also differences in the social behavior between children of different levels of power. As preschool children are in a critical developmental window when social knowledge is being accumulated and social skills are being acquired, using power relations within the kindergarten classroom as an entry point to analyze the impact of teachers' emotions on children's social behavior provides a new breakthrough for the professional development of early childhood education and the better achievement of educational goals.